Intracranial complete response for non‐small‐cell lung cancer patient with negative PD‐L1 expression of the lung using nivolumab. Issue 2 (27th May 2021) - Kitadai, Rui; Zenke, Yoshitaka; Hishima, Tsunekazu; Hosomi, Yukio
Abstract: Background: Nivolumab has shown promising results against non‐small‐cell lung cancer (NSCLC). However, its efficacy to treat central nervous system (CNS) metastases, specifically among programmed cell death 1 ligand 1 (PD‐L1)‐negative patients, remains unclear. Case: A 66‐year‐old woman was diagnosed with adenocarcinoma stage II and underwent a left lower lobectomy. The histopathological evaluation revealed stage IVA with pleural dissemination. The patient did not harbor an epidermal growth factor receptor (EGFR) mutation or anaplastic lymphoma kinase (ALK) rearrangement, and PD‐L1 expression of the surgical specimen using 22C3 assay was 0%. Single brain metastasis was detected, and carboplatin and nab‐paclitaxel were administered. After three cycles, asymptomatic multiple brain metastases were identified, and the patient was treated with nivolumab as second‐line chemotherapy. Six months later, MRI revealed an intracranial complete response (CR). Nivolumab was discontinued after 23 cycles due to immune‐related adverse events (irAEs) of grade 2 rash. However, its effects were sustained for 13 months after discontinuation. We were unable to evaluate the PD‐L1 expression of brain metastases, which may show heterogeneity. Conclusion: This case demonstrates that nivolumab effectively treated a patient with negative PD‐L1 expression of the lung harboring CNS metastases.